2021
DOI: 10.1101/2021.12.06.471424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transactive response DNA-binding Protein (TDP-43) regulates early HIV-1 entry and infection

Abstract: The transactive response DNA-binding protein (TDP-43) is an important regulator of mRNA, being reported to stabilize the anti-HIV factor, histone deacetylase 6 (HDAC6). However, little is known about the role of TDP-43 in HIV infection. In this work, we seek for the TDP-43 function on regulating CD4+ T cell permissibility to HIV infection. We observed that over-expression of wt-TDP-43 in CD4+ T cells stabilized HDAC6, increasing mRNA and the protein levels of this antiviral enzyme. Under this experimental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 54 publications
(101 reference statements)
2
10
0
Order By: Relevance
“…Our results indicate that the ZIKV NS5 protein mainly accumulates in nuclear structures, as previously reported [64,65,117,118], and promotes the acetylation of MTs that aberrantly reorganize in nested-like structures organized at the cell periphery. Similarly, we observed that the p62 protein, a marker of autophagy flux [97][98][99][100][101][102][103], accumulated in cells overexpressing the ZIKV NS5 protein. Notably, these data indicate that NS5 alters cell events that are under the control of the antiviral tubulin deacetylase and the autophagyassociated enzyme HDAC6 [91,[98][99][100][101][104][105][106][107][108]].…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Our results indicate that the ZIKV NS5 protein mainly accumulates in nuclear structures, as previously reported [64,65,117,118], and promotes the acetylation of MTs that aberrantly reorganize in nested-like structures organized at the cell periphery. Similarly, we observed that the p62 protein, a marker of autophagy flux [97][98][99][100][101][102][103], accumulated in cells overexpressing the ZIKV NS5 protein. Notably, these data indicate that NS5 alters cell events that are under the control of the antiviral tubulin deacetylase and the autophagyassociated enzyme HDAC6 [91,[98][99][100][101][104][105][106][107][108]].…”
Section: Introductionsupporting
confidence: 56%
“…Similarly, we observed that the p62 protein, a marker of autophagy flux [97][98][99][100][101][102][103], accumulated in cells overexpressing the ZIKV NS5 protein. Notably, these data indicate that NS5 alters cell events that are under the control of the antiviral tubulin deacetylase and the autophagyassociated enzyme HDAC6 [91,[98][99][100][101][104][105][106][107][108]]. HDAC6 appears to degrade NS5 by autophagy in a deacetylase-and BUZ (binder of or bound to ubiquitin zinc finger [119,120]) domain-dependent manner and by controlling the cytoplasmic expression of NS5.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations